A pomegranate-inspired B@(NH4)2SiF6@LiClO4 architecture for spatiotemporally coordinated boron combustion - Jiayan Liang; Hongyu Zhang; Jian Zhang; Xuwen Wang; Yangming Wang; Hao Bai; Yi Rong; Kaifeng Lin; Debin Xia; Yulin Yang (Chemical Engineering Journal, 2026)

2,6-Dibromophenol inhibits fin regeneration in zebrafish larvae via Wnt-mediated immune cell recruitment - Yuhan Huang; Wenya Tie; Zijian Li; Nannan Wang; Jiayan Xiong; Li Lin; Yuan Kong; Yunyi Mo; Minting Li; Jianpeng Liu; Zhonghao Xiao; Weitao Hu; et al. (Fish & Shellfish Immunology, 2026)

Sex-specific expression of detoxification proteins contributes to differential metabolic detoxification capacity and acaricide sensitivity in female and male Tetranychus cinnabarinus (Boisduval) - Sihan Chen; Weiwei Sun; Jiayan Duan; Ya Yang; Zhixin Jiang; Mingpeng Wang; Zhifeng Xu; Lin He; Kaiyang Feng (Pesticide Biochemistry and Physiology, 2026)

Faecalibaculum rodentium- derived quinic acid- mediated Treg differentiation drives the attenuation intestinal inflammation by Agrimoniae Herba polysaccharides - Jiayan Hu; Yitong Yu; Zhibin Wang; Muyuan Wang; Yuxi Wang; Xiaowei Chen; Yuyue Liu; Mengyu Zheng; Chengtao Liang; Chenran Lv; Anqi Yang; Zhengdao Lin; et al. (Carbohydrate Polymers, 2026)

Tandem synergy of hydroxyl radicals and nonradical ferryl for efficient photo-self-Fenton mineralization of refractory pollutants - Ailing Zhang; Meili Liu; Weiqin Wei; Wenwen Jing; Jiayan Teng; Yuanshen Qin; Lin Jing; Yongfa Zhu; Hongxing Dai; Jiguang Deng; Zhen Wei (Water Research, 2026)

DOM-mediated inhibition of ciprofloxacin photodegradation: Dual roles of antioxidant quenching and triplet-state interactions - Jihong Xu; Weiwen Sun; Jiayan Ding; Yong Huang; Xi Chen; Lin Li; Cheng Peng; Lushi Lian; Xiaohong Guan (Water Research, 2026)

Three new terpenes with potential antibacterial and anti-COVID-19 activities from the stems of Eurya chinensis R. Br - Chen Liping; Lin Shaodan; Pan Yongchen; Huijun Liang; Chen Jiayan; Xin Lian; Li Guangying; Xiong Xiubi; Jie Yuan; Jiewei Wu (Natural Product Research, 2026)

Global Patterns and Drivers of Recent Decoupling Between Extratropical Spring Phenology and Temperature - Ziyu Lu; Ming Shao; Jiayan Li; Jingyuan Lin; Peiyuan Tao; Mengyu Li; Siqi Zhang; Peng Yao; Yang Fu (Global Change Biology, 2026)
While spring phenology has been widely studied, the magnitude and drivers of its decoupling from thermal cues across extratropical biomes remain poorly understood. Using satellite data from 1982 to 2021, we show that the onset of vegetation green‐up (GSOS) generally lags the onset of the thermal growing season (TSOS). This mismatch (ΔSOS) has increased by 1.51 days per decade ( p 15 days), warming‐driven advances in TSOS are increasingly decoupled from GSOS, as declining precipitation and enhanced evaporative demand intensify moisture limitation and delay green‐up; in temperate forests (both coniferous and broadleaf), warming together with enhanced shortwave radiation promotes faster GSOS advancement relative to TSOS, thereby dampening the mismatch. These contrasting pathways reveal an accelerating yet heterogeneous phenology–temperature decoupling, with far‐reaching consequences for ecosystem synchrony, seasonal carbon uptake, and land–climate feedbacks. Our results underscore the need to incorporate non‐thermal drivers and biome‐specific controls into phenological and Earth system models to better constrain future climate–biosphere interactions.

Unlocking controllable ignition and combustion in onion-structured Al@Na3AlF6@AP composites through Na3AlF6 “Temperature Switch” - Xuwen Wang; Jian Zhang; Hao Bai; Changsheng Tang; Jiayan Liang; Zhe Shi; Kaifeng Lin; Debin Xia; Bowen Tao; Fang Du; Yulin Yang (Fuel, 2026)

Rhizosphere remediation of saline-alkali soils by Helianthus tuberosus: Linking microbial-metabolite synergies to carbon sequestration - Tianyun Shao; Yang Yue; Wenhan Dong; Jiayan Lin; Yilong Ma; Zhaosheng Zhou; Xiumei Gao; Hui Guo; Xiaohua Long; Ju zhao; Yu Zhang (Science of The Total Environment, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

Inter-individual variation in human microbiota drives differential impacts on the fermentability of insoluble bran by soluble β-glucans from whole barley - Songtao Fan; Yiwei Ding; Zikang Hu; Zhihong Zhang; Lin Fu; Jiayan Zhang; Ying Zhu; Juan Bai; Xiang Xiao (Food Hydrocolloids, 2025)

Isolation and identification of an undescribed monoterpenoid naphthoquinone from Streptomyces diacarni LHW51701 - Jie Wang; Jiayan Pan; Yuanyuan Ji; Xinkai Wang; Huilin Chen; Qiongyan Fang; Weihua Jiao; Yongjun Zhou; Houwen Lin; Lili Hong (Phytochemistry Letters, 2025)

The modifying role of residential greenness on the association between heat waves and adverse birth outcomes: Results from the ELEFANT project - Yuxuan Ma; Yuanyuan Yu; Lei Zhao; Qisijing Liu; Jiayan Ni; Zi Lin; Bin Chen; Weixia Li; Huishu Lin; Yuhong He; Shuhao Shi; Jianqiong Zheng; et al. (Environmental Research, 2025)

Breaking separation bottleneck in sucralose production: Clarifying the obscure mechanism and pre-embedding second solvents for highly selective separation of chlorinated product - Xiaoping Chen; Jiayan Lei; Zhoulin Lv; Zi'ang Chen; Shitong Lin; Zhenming Guo; Huadong Luo; Yingshu Wang; Jingjing Chen; Haohong Li; Huidong Zheng (Chemical Engineering Journal, 2025)

Sodium Selenite Prevents Matrine-Induced Nephrotoxicity by Suppressing Ferroptosis via the GSH-GPX4 Antioxidant System - Xi Wang; Zixiong Lin; Ting Li; Wenjing Zhu; Hanxin Huang; Jiayan Hu; Jie Zhou (Biological Trace Element Research, 2024)

Transmission characteristics and the factors influencing stable oxygen isotopes in precipitation, soil water, and drip water in Remi Cave, Western Hunan, China - Yiping Tian; Yunxia Li; Jiayan Li; Chenxi Yang; Angli Du; Miaofa Li; Xinping Zhang; Lin Zhao; Lidan Liu; Zhiguo Rao (Journal of Hydrology, 2024)

Nitrite self-degradation process in radish paocai under the synergistic regulation of prokaryotic microorganisms - Xinyu Hu; Wei Wei; Jiayan Zhang; Songtao Fan; Yufeng He; Juan Bai; Ying Zhu; Yansheng Zhao; Lin Zhu; Xiang Xiao (Food Bioscience, 2024)

Occurrence, Degradation Pathways, and Potential Synergistic Degradation Mechanism of Microplastics in Surface Water: A Review - Lihua Niu; Yingjie Wang; Yi Li; Li Lin; Yamei Chen; Jiayan Shen (Current Pollution Reports, 2023)

Capsule structured Al/FeF3/AP energetic microspheres with enhanced combustion performance and energy release efficiency by a microexplosion reaction - Xuwen Wang; Yinghui Hu; Jian Zhang; Jiayan Liang; Yulin Yang; Kaifeng Lin; Aimin Pang; Yong Shuai (Fuel, 2023)

Simultaneous adsorption and biodegradation of polychlorinated biphenyls using resuscitated strain Streptococcus sp. SPC0 immobilized in polyvinyl alcohol‑sodium alginate - Qihua Lin; Jiayan Ding; Yingying Yang; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Science of The Total Environment, 2023)

Recent advances in targeted manipulation of the gut microbiome by prebiotics: from taxonomic composition to metabolic function - Songtao Fan; Zhihong Zhang; Yansheng Zhao; Maria Daglia; Jiayan Zhang; Ying Zhu; Juan Bai; Lin Zhu; Xiang Xiao (Current Opinion in Food Science, 2023)

Structural analysis of glycosaminoglycans from Colla corii asini by liquid chromatography-electrospray ion trap mass spectrometry - Haiyue Huang; Su Liu; Jiayan Du; Jianghui Lin; Quntao Liang; Shutao Liu; Zheng Wei (Glycoconjugate Journal, 2020)

Analysis of Heparan sulfate/heparin from Colla corii asini by liquid chromatography-electrospray ion trap mass spectrometry - Jiayan Du; Su Liu; Quntao Liang; Jianghui Lin; Lilong Jiang; Fener Chen; Zheng Wei (Glycoconjugate Journal, 2019)

Radiometric calibration evaluation for RSBs of Suomi-NPP/VIIRS and Aqua/MODIS based on the 2015 Dunhuang Chinese Radiometric Calibration Site in situ measurements - Lin Chen; Peng Zhang; Jiayan Lv; Na Xu; Xiuqing Hu (International Journal of Remote Sensing, 2017)

Targeting roles of inflammatory microenvironment in lung cancer and metastasis - Lin Shi; Lingyan Wang; Jiayan Hou; Bijun Zhu; Zhihui Min; Miaomiao Zhang; Dongli Song; Yunfeng Cheng; Xiangdong Wang (Cancer and Metastasis Reviews, 2015)

The Kuroshio Extension: a leading mechanism for the seasonal sea-level variability along the west coast of Japan - Chao Ma; Jiayan Yang; Dexing Wu; Xiaopei Lin (Ocean Dynamics, 2010)